Leadership style comparison: Iowa community college presidents and superintendents and the ideal leadership style perceived by the board presidents of these organizations - Tedesco, Paul Thomas, author; Davies, Timothy Gray, advisor; Carlson, Laurie A., committee member; Cooner, Donna, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2004)
This study focused on one aspect of educational leadership called leadership styles to determine if any significant statistical differences in leadership style exist between Iowa community college presidents and K-12 superintendents. A second research question to determine if any significant statistical difference existed in the ideal leadership style for these positions as perceived by the board presidents at Iowa community colleges and K- 12 districts. The study focus was a shortage of administration and the possibility of alleviating the shortage by expanding to K-14 governance. Bolman and Deal's (1997) Leadership Orientation Questionnaire was used as it measures four leadership styles: structural, human resource, political and symbolic. The results found a difference in symbolic leadership style preference with the community college president more likely to use this style of leadership. No differences were discovered in the ideal leadership styles identified by the board presidents. Therefore, the door is open to further study about instituting a K-14 governance structure in Iowa.
Keywords: school administration; community colleges; higher education; educational administration; community college education